2004
DOI: 10.1111/j.1572-0241.2004.40009.x
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocyte Apoptosis, Expression of Death Receptors, and Activation of NF-κB in the Liver of Nonalcoholic and Alcoholic Steatohepatitis Patients

Abstract: Liver injury in NASH and ASH is associated with increased hepatocyte apoptosis mediated by death receptors. Further, apoptosis correlates with active NF-kappaB expression, and disease severity. This potential mechanistic link might provide multiple interesting targets for therapeutic intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
222
0
8

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 357 publications
(247 citation statements)
references
References 44 publications
17
222
0
8
Order By: Relevance
“…JNK contributes to insulin resistance via direct phosphorylation and degradation of IRS1, dampening the intracellular signalling pathway downstream of the insulin receptor [52]. NF-κB activation has been demonstrated in the liver of patients with NASH [55], and leads to increased transcription of numerous proinflammatory genes that amplify the response [52]. In the presence of systemic inflammation, the liver is again both the target of and contributor to inflammatory changes.…”
Section: Biological Mechanisms Potentially Responsible For Acceleratementioning
confidence: 99%
“…JNK contributes to insulin resistance via direct phosphorylation and degradation of IRS1, dampening the intracellular signalling pathway downstream of the insulin receptor [52]. NF-κB activation has been demonstrated in the liver of patients with NASH [55], and leads to increased transcription of numerous proinflammatory genes that amplify the response [52]. In the presence of systemic inflammation, the liver is again both the target of and contributor to inflammatory changes.…”
Section: Biological Mechanisms Potentially Responsible For Acceleratementioning
confidence: 99%
“…Interestingly, cell death by apoptosis may also constitute an important component of disease progression [4]. In fact, members of our team and others have already demonstrated that hepatocyte apoptosis is a prominent pathological feature in patients with NASH and NAFLD [5,6]. Nevertheless, the exact mechanisms of hepatocyte apoptosis in NASH and underlying factors of NAFLD progression and pathogenesis remain incompletely understood.…”
Section: Introductionmentioning
confidence: 99%
“…However, at least 1 report has revealed remarkably elevated hepatic NF-B activity in alcoholic liver disease, which correlates with the degree of inflammation and fibrosis. 9 Injury-induced activation of hepatic NF-B is observed in a variety of nonparenchymal and parenchymal liver cells, indicating that NF-B plays a central role in coordinating the inflammatory and wound healing response by stimulating gene transcription in multiple key cellular players. Kupffer cells (the liver's resident macrophages) display powerful NF-B activation in response to liver injury by alcohol, carbon tetrachloride, endotoxin, and cholestasis, resulting in production and secretion of proinflammatory cytokines (including the hepatomitogens TNF-␣ and IL-6) that are strongly implicated as promoters of fibrosis and HCC.…”
Section: The Inflammation-fibrosis-cancer Axismentioning
confidence: 99%